Microstructure and properties analysis of the brazing alloy prepared from recycled E-waste - Yang, Jiao; Bao, Li; Long, Weimin; Zhong, Sujuan; Qin, Jian; Qiao, Ruilin (Frontiers in Chemistry, 2022)
In order to realize the efficient and comprehensive utilization of e-waste resources and short process preparation of alloy brazing materials, this study has analyzed the microstructure and properties of e-waste recycled brazing alloys by the analysis methods of inductively coupled plasma emission spectrometer, differential scanning calorimeter, scanning electron microscope, metalloscope, X-ray diffractometer, micro-hardness tester. Experimental results showed that phase compositions are significant differences between the alloys prepared by the recycled e-waste and the pure metals. The circuit board recycling alloy mainly consisted of α-Fe dendrites, (Cu, Sn) phases, Sn-rich phases and Cu matrix, while the alloy obtained by pure metals is composed of (Cu, Sn) phase, Sn-rich phase and Cu matrix. The melting temperature of alloy obtained by melting the circuit board is in the range of 985.3°C–1,053.0°C, which was wider and higher than that of alloy obtained by pure metal smelting. The shear strengths of the joints brazed by the brazing alloys prepared by the recycle e-waste and pure metals are 182.21 MPa and 277.02 MPa, respectively. There is little difference in hardness between the two types of brazed joints. In addition, there are a large number of precipitated phases in alloy obtained by the recycled circuit board, owing to the precipitation strengthening mechanism. The main strengthening mechanism of alloy obtained by pure metals is solid-solution strengthening. The paper focused primarily on alloy obtained by melting the circuit board and studying the specific composition, melting temperature, structure, and properties of alloys formed by melting the circuit board and pure metals. Meawhile, the size, morphology and other microstructure evolution of the second phase of brazing alloy were investigated to provide theoretical guidance for the brazing alloy in the subsequent actual production process.